2010
DOI: 10.1161/atvbaha.110.212308
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic Acid Prevents Neointimal Hyperplasia Via Induction of p38 Mitogen-Activated Protein Kinase/Nur77-Mediated Apoptosis of Vascular Smooth Muscle Cells and Accelerates Postinjury Reendothelialization

Abstract: Objective-To explore whether ␣-lipoic acid (ALA), a naturally occurring antioxidant, inhibits neointimal hyperplasia by inducing apoptosis of vascular smooth muscle cells and to examine its potential effects on reendothelialization and platelet aggregation. Methods and Results-Restenosis and late stent thrombosis, caused by neointimal hyperplasia and delayed reendothelialization, are significant clinical problems of balloon angioplasty and drug-eluting stents. ALA treatment strongly induced apoptosis of vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…A number of molecules including α-lipoic acid, caffeic acid phenethyl ester, and nifedipine have been recognized for their anti-proliferative effects on VSMCs mediated by ROS reduction [20][21][22][23]. DPP-4 inhibitors such as sitagliptin, anagliptin, and alogliptin have been shown to reduce atherosclerotic lesions in apoE−/− mice by inhibiting proinflammatory responses and endothelial cell apoptosis, thereby preventing the cardiac malfunction associated with ROS production [9,10,24,25].…”
Section: Antioxidant Effect On Abnormal Vascular Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of molecules including α-lipoic acid, caffeic acid phenethyl ester, and nifedipine have been recognized for their anti-proliferative effects on VSMCs mediated by ROS reduction [20][21][22][23]. DPP-4 inhibitors such as sitagliptin, anagliptin, and alogliptin have been shown to reduce atherosclerotic lesions in apoE−/− mice by inhibiting proinflammatory responses and endothelial cell apoptosis, thereby preventing the cardiac malfunction associated with ROS production [9,10,24,25].…”
Section: Antioxidant Effect On Abnormal Vascular Remodelingmentioning
confidence: 99%
“…Previously, we reported that various types of drugs such as α-lipoic acid and dimethyl fumarate have been identified as Nrf2 activators with protective effects against abnormal vascular remodeling via restoration of mitochondrial function [20,37]. In many studies, cardiovascular diseases such as hypertension, atherosclerosis, and heart failure have been shown to be associated with abnormal vascular remodeling following vascular damage to the fundamental interactions between endothelial cells and VSMCs.…”
Section: The Beneficial Effects Of Gemigliptinmentioning
confidence: 99%
“…Most recently, it has been demonstrated that ␣-lipoic acid inhibits neointima formation in rat carotid arteries after ballooninjury, involving enhanced SMC apoptosis. In this study it is shown that ␣-lipoic acid enhances the expression and cytoplasmic, rather than nuclear, localization of Nur77 in the cell, which triggered apoptosis [11]. Knockdown experiments both in cultured SMCs and in the rat model revealed crucial involvement of Nur77 in ␣-lipoic acid-induced SMC apoptosis.…”
Section: Nur77 In Vascular Smcsmentioning
confidence: 71%
“…Knockdown experiments both in cultured SMCs and in the rat model revealed crucial involvement of Nur77 in ␣-lipoic acid-induced SMC apoptosis. Interestingly, it was also shown that ␣-lipoic acid enhances endothelial cell proliferation [11].…”
Section: Nur77 In Vascular Smcsmentioning
confidence: 99%
“…Moreover, ALA inhibits neointimal proliferation and late stent thrombosis after percutaneous transluminal coronary angioplasty [40,41]. ALA-coated stents suppress neointimal proliferation in a porcine coronary restenosis model [42].…”
Section: Micro-ct Analysismentioning
confidence: 99%